Promoting Protesters' Compliance: The Effect of General Perceptions of the Police versus Police Actions. (27th June 2020) - Perry, Gali
Abstract: Public willingness to comply with the police is desirable in democratic societies, and even more so in high-risk policing tasks such as protest policing. To allow freedom of speech while maintaining public order, officers require protesters to follow orders and cooperate. The process-based model of policing suggests that protesters' compliance will be mainly affected by their general perceptions of the police—primarily, trust in the police and perceptions of just policing procedures. In conjunction, police actions during a demonstration and the dynamics between officers and protesters can also affect protesters' willingness to comply. This study uses a series of Ordinary Least Squares (OLS) regression models to analyse survey responses of 470 protesters who participated in the 'Occupy' protests in Israel during 2012. Findings suggest that positive evaluations of trust in the police and policing procedures correlate with compliance; however, when protesters perceived police actions as negative, they were less willing to comply.